Influence of the yielding criterion on total forming force in metallic junctions using elastomers - Foli, Cristiano Roberto Martins; Menezes, Miguel Angelo; Moreira Filho, Lindolfo Araujo (Elsevier B.V., 2006)
The production of metallic junctions employing elastomers is an unconventional technique that has been in development in the last 20 years. The forming process gets successfull just if a simultaneous compression between the elastomers and the tube takes place. Exact solutions for problems involving forming with elastomers are quite difficult to determine. However, the upper-bound theory can be used in order to predict the necessary load for junctions forming. Thus, it is necessary to develop a model capable to provide an estimate of the total forming force, which is useful to set-up tools and equipments required for the process. In this work, Von Mises, Hill's 1948 and Hill's 1979 associated yielding theories, and the Hosford's theory (1979) as well, were used in order to study the anisotropic behaviour on total forming force of junctions using elastomers, insuring the functionality of the proposed model. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: junctions; elastomers; yielding criterion; anisotropy; forming